2018
DOI: 10.1289/isee.2017.2017-254
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Acrylamide Intake during Pregnancy and Postnatal Growth and Obesity: Results from the Norwegian Mother and Child Cohort Study (MoBa)

Abstract: Background: Prenatal acrylamide exposure has been negatively associated with fetal growth but the association with child growth is unknown. Objectives: We studied the association between prenatal acrylamide exposure and child postnatal growth up to 8 years in the Norwegian Mother and Child Cohort Study (MoBa). Methods: In 51,952 mother-child pairs from MoBa, acrylamide intake during pregnancy was estimated by combining maternal food intake with food concentrations of acrylamide. Mothers reported their child's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Three longitudinal studies have shown a relationship between higher maternal acrylamide exposure and lower birth weight or higher risk of having a small for gestational age baby 123 124 To our knowledge one study showed a positive association between acrylamide exposure and postnatal growth 125 …”
Section: Introductionmentioning
confidence: 83%
“…Three longitudinal studies have shown a relationship between higher maternal acrylamide exposure and lower birth weight or higher risk of having a small for gestational age baby 123 124 To our knowledge one study showed a positive association between acrylamide exposure and postnatal growth 125 …”
Section: Introductionmentioning
confidence: 83%
“…A recent study indicated the significant associations between AA exposure level and the likelihoods of allergy-related outcomes in the general US population (6) . The biological mechanisms for the effects of AA on Study or Subgroup Kadawathagedara et al (10) Kadawathagedara et al (10) b Kadawathagedara et al (10) c Kadawathagedara et al (9) a Kadawathagedara et al (9) b Kadawathagedara et al (9) c Nagata et al (12) e Nagata et al (12) f Pedersen et al (11) a Pedersen et al (11) b Pedersen et al (11) c Total (95 % CI) Heteogeneity: Tau Kadawathagedara et al (10) a Duarte-Salles et al (8) a Duarte-Salles et al (8) b Duarte-Salles et al (8) c Kadawathagedara et al (10) b Kadawathagedara et al (10) c Pedersen et al (11) Total (95 % CI) Heteogeneity: Tau Nagata et al (12) e Nagata et al (12) f Pedersen et al (11) a Pedersen et al (11) b…”
Section: Discussionmentioning
confidence: 99%
“…A total of 1028 articles were identified, and after removal of duplicates (n 474), 554 articles remained. After title and abstract screening and full-text review, five full-text studies (8)(9)(10)(11)(12) met the inclusion criteria and were remained for the present meta-analysis.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations